2019
DOI: 10.3390/ijerph16071198
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Climate in Sport Is Associated with Life Stress Levels, Academic Performance and Physical Activity Engagement of Adolescents

Abstract: The present study sought to define and contrast an explanatory model incorporating motivational climate towards sport, life stress, academic performance, and engagement in physical activity, and to analyze the existing relationships between these variables as a function of sex. A total of 2452 adolescents of both sexes (42.7% males and 57.3% females) participated in the present study, with self-reported ages between 13 and 16 years (M = 14.43; SD = 1.15). Participants were from Granada (Spain) and perceived mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 66 publications
(71 reference statements)
1
28
0
Order By: Relevance
“…This may indicate that these students are protected from boredom and sadness by being in permanent contact with physical activity and sport. This has been established in various research studies that suggest that belonging to a sporting environment [70][71][72] helps individuals in their critical development, including Castro et al's conclusions on their study in which they highlight that a task-involving climate and engagement in physical activity are both associated with lower levels of life stress and higher levels of academic performance [73]. Likewise, prior research [74,75] has demonstrated the importance of psychological needs to the development and wellbeing of individuals.…”
Section: Discussionmentioning
confidence: 87%
“…This may indicate that these students are protected from boredom and sadness by being in permanent contact with physical activity and sport. This has been established in various research studies that suggest that belonging to a sporting environment [70][71][72] helps individuals in their critical development, including Castro et al's conclusions on their study in which they highlight that a task-involving climate and engagement in physical activity are both associated with lower levels of life stress and higher levels of academic performance [73]. Likewise, prior research [74,75] has demonstrated the importance of psychological needs to the development and wellbeing of individuals.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, in line with our results, Barbosa, Tristán, Tomás, González and López [ 43 ] found no relationship between extrinsic goal orientation and the different dimensions of academic burnout. Other studies argued that task orientation is more strongly correlated with academic performance than ego orientation [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are studies that have demonstrated the negative relationship between overweightness and obesity and psychological consequences such as self-concept [4]. Levels of self-concept represent protective factors against the development of maladaptive behaviors in scholars [30]. Research studies demonstrate that adolescents, both males and females, who participate regularly in PA report a more positive physical self-concept than those who are not as active [17,18,20,21].…”
Section: Introductionmentioning
confidence: 99%